Torremolinos, analysis of hotel land urban change in a mature seaside destination - Almeida-García, Fernando; Cortés-Macías, Rafael; Peláez-Fernández, María Ángeles; Balbuena-Vázquez, Antonia (My University, 2015)
The city of Torremolinos was one of the pioneering spaces in the implementation of mass tourism of sun and beach on the Costa del Sol, Spain. The town of Torremolinos in 2014 had a population of 67,353 inhabitants, an area of 19.8 km2. The city is located in the province of Malaga in the Costa del Sol. The objectives of this study are approaching the study of the implementation of the hotels in Torremolinos and its integration into the urban system of the municipality. The changes in land use are analyzed during the fifty years of the study. We aim to characterize the urban-regional model generated by the hotel implantation as singular element Torremolinos growth Method To achieve these objectives has produced a digital mapping of urban growth in Torremolinos (ArcGis.10). We have conducted a mapping of the evolution of urban areas and the location of the hotel industry, from aerial orthophotos. Regarding the layer hotels, we have made the digitization of occupied facilities and buildings of the hotel area. To do this operation, we have used the Register of Hoteliers of the Junta de Andalucía (Regional Government) and we have located hotels with the help of Google Maps and StreetView. We have conducted a cluster analysis about the hotel supply of Torremolinos. Results and conclusions Between 1957 and 1977, was built most of the tourist area of Torremolinos, especially hotels and apartments. In these twenty years urbanization rate was 36.1 ha / year, which was reflected: (i) intense growth of dense urban area (it has tripled from 75.9 to 242.4 ha.. ); (ii) expansion of housing developments that quintupled its surface and above all, (iii) strong increase in other developed areas (5,598.2%), linked to infrastructure. The rate of urbanization and construction was more moderate in the following periods. In the analysis period (1959-2010) we observed that the average plot of hotels has increased: from 10,000 m2 to 20,000 m2. This increase was a business strategy to maintain low profit margin of hotels for mass tourism. Cluster analysis identified two main hotel groups: the seaside front cluster and backside group. This study shows the evolution of a mature destination for sun and beach, which has maintained over time its hotel activity.
Torremolinos, análisis de cambios urbanos hoteleros en un destino de sol y playa
Presentación de la comunicación del congreso.
Keywords: Turismo; Torremolinos; Urban change; Hotel; Seaside destination; Cluster analysis